The future of empirical research in and through the Dutch Reformed Church - C. Van Wyngaard (Acta Theologica)
This article is my contribution to a Festschrift for Kobus Schoeman. It focuses attention on Schoeman’s relationship with the Dutch Reformed Church’s (DRC) empirical research work. It situates Schoeman within the DRC and provides an overview of the empirical research projects from within the DRC and to which Schoeman contributed uring his career. The article outlines Schoeman’s analysis of the state of the DRC. The article then discusses three foci that will require more attention in the coming years within the empirical research agenda of the DRC. These foci include situating the DRC within a broader ecumenical environment through empirical research; attending to more critical analyses in the interpretation of empirical data, and revisiting historic empirical research data to examine longitudinal attitudinal shifts in the DRC.